Consumption of healthy and unhealthy foods by the African poor: Evidence from Nigeria, Tanzania, and Uganda - Dolislager, Michael; Liverpool‐Tasie; Lenis Saweda O; Mason, Nicole M; Reardon, Thomas; Tschirley, David (Wiley Subscription Services, Inc, 2022)
AbstractWe use national Living Standards Measurement Study (LSMS) datasets fromNigeria, Tanzania, and Uganda to examine consumption by the rural and urbanpoor of “unhealthy foods” (including ultra-processed foods such as sweets andsugary beverages) versus “healthy foods” beyond starchy staples (such as vegeta-bles, beans, animal products, and fruits). Consumption of processed foods andnonstaples is often associated in policy discussion in Africa with middle-classurban consumers rather than the poor. We analyzed household food consump-tion expenditure with Locally Weighted Scatterplot Smoothing (LOWESS)curves and augmented Engel regressions. We found that substantial shares ofthe consumption expenditure of the poor, both rural and urban, are on healthyand unhealthy foods. We found, surprisingly, that the poor’s food consumptionpatterns do not differ sharply from the middle classes’, in rural and urban areas,except for the case of ultra-processed foods of which the poor still consumemuch less than the middle class. We found that the poor dedicate 25% of theirfood consumption expenditure to the category vegetables/beans, versus 22%and 17% by the lower-middle and upper-middle-income strata. Fruits/animalproducts constitute 17% of the poor’s consumption expenditure compared to 23%and 27% by the lower- and upper-middle strata. Ultra-processed food (e.g., sugar-sweetened beverages) form 12% of the consumption of the poor, versus 20% and32% for the lower- and upper-middle strata. Shares are increasing with incomestarting at incomes well below the poverty line. Nonincome factors play impor-tant roles: e.g., rural off-farm employment is associated with more consumptionexpenditure of processed foods by the poor due to the opportunity cost of time. KEYWORDS -Africa, consumption, expenditure, fish, food away from home, fruit and vegetables, meat,processed food, rural, the poor, urban. JEL CLASSIFICATIOND12, J20, O12, O18, Q12, Q18
Keywords: Africa, consumption, expenditure, fish, food away from home, fruit and vegetables, meat,processed food, rural, the poor, urban